(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
Macrolophus caliginosus (Hemiptera: Miridae) is a zoophytophagous predator widely used in integrated pest management programs in both greenhouse and open-field . Mass rearing of Macrolophus caliginosus is greatly dependent on Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs as food source. Moreover, the addition of this factitious prey after the inoculative releases of Macrolophus caliginosus under field conditions is recommended to facilitate establishment of this mirid. However, E. kuehniella eggs are expensive and availability is limited. One possible strategy to reduce the amount of E. kuehniella eggs needed is the provision of sugar.This study was conducted during the period between May and November in 2014 in the labs of the Lattakia center of rearing bio enemis. In this work, the effect of sucrose as nutritional supplement on selected life-history traits of M.caligenosus was studied. The addition of sucrose (100 g/l) ad libitum to a diet of E. kuehniella eggs significantly increased the progeny of Macrolophus caliginosus and did not affect survival of nymphs nor developmental time. Moreover, addition of sucrose significantly reduced the number of E. kuehniella eggs consumed. These results may have practical implications of interest in mass rearing systems of M.caliginosus and its management in fields and greenhouses as a part of integrated control programs. يعد المفترس(Hemiptera: Miridae) Macrolophus caliginosus من المفترسات المهمة التي يمكن استخدامها في برامج الإدارة المتكاملة للآفات ، خاصة آفات الزراعات المحمية . تعتمد التربية الكمية للمفترس بشكل أساسي على بيوض حشرة(Lepidoptera: Pyralidae) Ephestia kuehniella Zeller بوصفها مصدراً للتغذية، يوصى أحياناً، عند الإطلاق الكمي لهذا المفترس في الحقل، بإضافة بيوض E.kuehniella لتسهيل استيطان المفترس. ونظراً لارتفاع كلفة إنتاج بيض E. kuehniella مخبرياً، تم البحث عن طريقة علمية و تطبيقية، يتم من خلالها تقليل كمية بيض E. kuehniella اللازمة لتربية المفترس، و إطلاقه في الحقل . أجريت هذه الدراسة خلال الفترة بين أيار و تشرين الثاني من عام 2014 في مختبرات مركز إكثار الأعداء الحيوية في اللاذقية . تمت دراسة تأثير التغذية السكرية بمعدل (100 غ/ ل) بوصفها مكملاً غذائياً، إضافة إلى بيض فراشة الطحين (بعد قتل حيويته)، دلت النتائج على وجود فروق معنوية بين مدة تطور أعمار الحورية في حال التغذية السكرية، و عدم وجود ها لكل من عمر الحورية الأول و الثاني و الرابع و الخامس. ولم تسجل فروق معنوية بالنسبة إلى عمر الحورية الثالث. في حين سجلت فروق معنوية في كمية البيض المستهلكة من قبل أطوار المفترس بلغت أقصاها لدى الحشرة الكاملة (200.16±3.96) بيضة/مدة حياة الحشرة الكاملة دون إضافة التغذية السكرية، و (129.52±3.31) بيضة/مدة حياة الحشرة الكاملة مع وجود التغذية السكرية . ربما تشير هذه النتيجة إلى إمكانية تخفيض كمية البيض المستخدم في تربية المفترس M.caliginosus ، مما يجعل استخدامه أكثر اقتصادية، وهذا يحتاج إلى دراسة موسعة أكثر .